A review of the use of Drastic in assesing the vulnerability of aquifers to contamination, and a case study of the use of Drastic on a localised scale in South Africa. - Vagis, Georgia Evgenia (My University, 2008)
ABSTRACT The use of DRASTIC – an aquifer vulnerability to contamination assessment tool, is analysed and reviewed for its applicability in helping develop a national aquifer management systems from the vulnerability maps produced by DRASTIC. Furthermore, the use of DRASTIC in assessing the vulnerability of an aquifer on a localised scale has been performed. The study showed that DRASTIC yields accurate results on localised scales where sufficient information is available. The use of DRASTIC on a national scale is subject to the scale of the input data and will only produce an aquifer vulnerability map that may be used as a general national development tool that cannot be applied to site specific developments.